Changes in gut microbiota after gastric cancer surgery: a prospective longitudinal study - Yuhua He; Shilin Gao; Lili Jiang; Jie Yang (Frontiers in Oncology)
BackgroundThis study was designed to characterize gut microbiota changes of the patients with gastric cancer before and after the gastrectomy during their hospital staying periods.Methods16S ribosomal RNA (rRNA) gene sequencing was used to evaluate differences in gut microbiota among patients with gastric cancer before and after the gastrectomy by comparing gut microbiota α diversity, β diversity, and structure composition at different taxonomic levels.ResultsA total of 120 fecal specimens were collected from 60 patients. There was no significant difference in Chao1 index, Shannon index, and Simpson index before and after gastrectomy (all P > 0.05). At the phylum level, the gut microbiota in the gastrectomy group showed less abundance of Bacteroidota, Synergistota, and Verrucomicrobiota but with higher abundance of Campylobacter, Actinobacteria, and Bacillota. At the genus level, the gut microbiota in the gastrectomy group showed less abundance of flora Bacteroides, Faecalibacterium, Blautia, and Lachnospiraceae nk4a136 group but with higher abundance of Campylobacter, Porphyromona, Finegordia, Dialist, Anaerococcus, and Corynebacterium.ConclusionsThere was no significant change in the diversity of intestinal flora before and after surgery. However, significant changes in the structure of intestinal flora before and after surgery were occurred.